2001
DOI: 10.1159/000052113
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Aortic Arch Plaques in Cryptogenic Stroke: A Microembolic Signal Monitoring Study

Abstract: Background and Purpose: To find out the prevalence of relevant atherosclerotic plaques in the aortic arch and their potential role as a source of embolism in cryptogenic stroke. Methods: We performed a transoesophageal echocardiography (TEE) on 49 patients with cryptogenic stroke from a total series of 212 non-selected patients with acute ischaemic stroke studied prospectively by cranial computed tomography (CT), colour-duplex and transcranial Doppler (TCD) sonography with micro-embolic signal (MES) monitoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 24 publications
1
26
0
1
Order By: Relevance
“…32,38,41,43 In addition, blood biomarkers, such as high pro-brain natriuretic peptide levels, may be predictors for incident AF in patients with cryptogenic stroke. [71][72][73] Aortogenic Embolic Source Evaluation TCD microembolism study showed that AAA has embolic potential, 74 and DWI patterns are characterized by multiple small scattered lesions in multiple vascular territories that are mainly located in cortical and borderzone regions. 75 These are in line with an autopsy study of cases with cerebral atheromatous embolism, which showed that atheromatous emboli containing mostly cholesterol crystals are associated with borderzone infarct, whereas large emboli containing fibrin are associated with large territory infarcts.…”
Section: Advanced Monitoring For Af Detectionmentioning
confidence: 99%
“…32,38,41,43 In addition, blood biomarkers, such as high pro-brain natriuretic peptide levels, may be predictors for incident AF in patients with cryptogenic stroke. [71][72][73] Aortogenic Embolic Source Evaluation TCD microembolism study showed that AAA has embolic potential, 74 and DWI patterns are characterized by multiple small scattered lesions in multiple vascular territories that are mainly located in cortical and borderzone regions. 75 These are in line with an autopsy study of cases with cerebral atheromatous embolism, which showed that atheromatous emboli containing mostly cholesterol crystals are associated with borderzone infarct, whereas large emboli containing fibrin are associated with large territory infarcts.…”
Section: Advanced Monitoring For Af Detectionmentioning
confidence: 99%
“…These results suggest that aortic atheroma of 3.5 mm or more may be a direct source of thromboemboli. Several studies using transcranial Doppler showed that embolic signals in the middle cerebral artery can be more frequently detected in patients with severe arch atheroma than in those without severe arch atheroma [19,20,21]. Severe atheroma along the aortic arch, therefore, can be a source of cerebral emboli.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6] Circumstantial evidence suggests that cerebral microemboli originate from the ulcerated arterial plaque. [7][8][9][10][11] Activated platelets play a crucial role in the generation of embolic events. Irrespective of the activating stimulus, the resulting platelet aggregation is mediated by glycoprotein IIb/IIIa (GPIIb/IIIa) receptors.…”
mentioning
confidence: 99%